Analysis of women’s education in India and its impact - K, Illakiya; Ratnam, Dr. S. Kanchana (IJRDO - Journal of Social Science and Humanities Research, 2018)
Women constitute almost half of the population of the world. Education for women is the way to improve the health, nutrition and economic status of the household that constitute the micro unit of a nation economy. In this context, it can be argued that lack of women education can be an impediment to the country’s economic development. This paper aims to study the Development of women’s education in India and its impact. Due to the lack of education, women for over thousand years have been marginalized and were silent and invisible in the public arena. Since female literacy is highly correlated with the health status of the population, lack of women education resulted in the increased infant mortality, maternal mortality, birth rate, death rate and decreased life expectancy at birth. At the same time, the lower Government initiatives and negative parental attitudes on women’s education that prevailed in the past resulted in lower Gross Enrolment Ratio and higher drop-out rates for girls at schools compared to boys. But since independence, with the Government initiatives and changing parental attitudes on the importance of women’s education, there is a rapid growth of female literacy rate in India. This increasing trends of female literacy over the decades resulted in the improved health status, higher Gross Enrolment Ratio and lower drop-out rates of girls at school.